Risk sharing and amplification in the global banking network - Leslie Sheng Shen; Tony Zhang (Federal Reserve Bank of Boston, 2024)
We develop a structural model of the global banking network and analyze its role in facilitating risk sharing and amplifying shocks across countries and over time. Using bilateral international lending data, we uncover significant heterogeneity in the willingness and capacity of banks to provide cross-border interbank and corporate loans. This heterogeneity explains variation in risk sharing and amplification across countries. Moreover, we show that cross-border loan supply has become less elastic over time, resulting in a decline in risk sharing. While shock amplification has also declined on average, some countries may experience greater amplification in response to foreign funding shocks.
Keywords: F34; G21; 330; global banking network; risk sharing; shock propagation; capital flows